Fumonisins, Trichothecenes and Zearalenone in Cereals - (:unkn) unknown (MDPI, 2008)
Fumonisins are phytotoxic mycotoxins which are synthesized by various species of the fungal genus Fusarium such as Fusarium verticillioides (Sacc.) Nirenberg (ex F. moniliforme Sheldon) and Fusarium proliferatum. The trichothecene (TC) mycotoxins are secondary metabolites produce by species that belong to several fungal genera, especially Fusarium, Stachybotrys, Trichothecium, Trichoderma, Memnoniella and Myrothecium. Fusarium mycotoxins are widely dispersed in cereals and their products. Zearalenone (ZEA) is an estrogenic compound produced by Fusarium spp. such as F. graminearum and F. culmorum. Fumonisins, the TCs and ZEA are hazardous for human and animal health. Contamination with TCs causes a number of illnesses in human and animal such as decrease in food consumption (anorexia), depression or inhibition on immune system function and haematoxicity. The purpose of this paper is to give a review of the papers published on the field of fumonisin, TC and ZEA mycotoxins in cereals consumed in the world.
Keywords: Fumonisins; trichothecenes; zearalenone; cereals; CORN-BASED FOOD; HIGH-RISK AREA; FUSARIUM MYCOTOXINS NIVALENOL; T-2 TOXIN; NATURAL OCCURRENCE; ESOPHAGEAL CANCER; OCHRATOXIN-A; FUSARENON-X; DIACETOXYSCIRPENOL ANGUIDINE; TISSUE DISTRIBUTION